Current State of Clinical Diagnosis and Treatment of Infantile Cytomegaloviral Hepatitis - 闫慧敏 甄小芳 舒静 柳静 (Chinese journal of integrative medicine, 2010)
Cytomegaloviral hepatitis is an infantile liver disease commonly encountered in China, which could be differentiated into 4 patterns with different clinical conditions. Along with the progress of laboratory diagnostic techniques, multiple diagnostic approaches are available for this disease, but accurate diagnosis can only be made when individual patients＇ realities are taken into consideration. Clinical treatments are various, and the Western medicine used is mainly anti-viral agents such as Ganciclovir, and so far no unified therapeutic program has been formed. More and more ways of regarding Chinese medicine treatment of cytomegaloviral hepatitis have been published increasingly in recent years, though further research to seek preferable treatment programs is still expected.